The Construction Of Quantum Block Cipher For Grover Algorithm - Eid, Almazrooie Mishal (2018)
Asymmetric and symmetric cryptography are believed to be secure against any attack using classical computers. However, this view is no longer valid in the presence of quantum computing. Asymmetric cryptographic algorithms which are based on integer factorization or discrete logarithms problems are rendered unsecured against quantum attacks. In contrast, threats posed by quantum computing to symmetric cryptography is not clear compared with asymmetric cryptography. Similarly to classical computing, to conduct a quantum attack on a classical block cipher, the block cipher must be designed and implemented as a quantum reversible circuit in a quantum platform.